2020
DOI: 10.1016/j.jsams.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exercise modality and menstrual cycle phase on circulating cardiac troponin T

Abstract: Objectives: It is unclear whether exercise modality (moderate-intensity continuous [MCE]; high-intensity interval [HIE]) and menstrual cycle phase (follicular [FP]; luteal [LP]), individually or in combination, mediate the commonly observed exercise-induced elevation in cardiac troponin T (cTnT). This study examines cTnT responses to MCE and HIE during both the FP and LP. Design: Randomised crossover study. Methods: Seventeen healthy, eumenorrheic women completed four trials including MCE (60% VO 2max steady-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…A meta-analysis in athletes with high training regime showed that acute and prolonged exercise was associated with larger LV volumes and a relative lower LV ejection fraction post intensive exercise [21]. In this study, the HT group showed a greater left cardiac remodelling process, which potentially gives athletes a better performance in a highly demanding race [11]; however, these changes could be related to a theoretically excessive and deleterious remodelling process [13], which is in keeping with other reports showing inflammatory and cell remodelling biomarkers elevation in athletes whose final significance are not fully clarified [22][23].…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis in athletes with high training regime showed that acute and prolonged exercise was associated with larger LV volumes and a relative lower LV ejection fraction post intensive exercise [21]. In this study, the HT group showed a greater left cardiac remodelling process, which potentially gives athletes a better performance in a highly demanding race [11]; however, these changes could be related to a theoretically excessive and deleterious remodelling process [13], which is in keeping with other reports showing inflammatory and cell remodelling biomarkers elevation in athletes whose final significance are not fully clarified [22][23].…”
Section: Discussionsupporting
confidence: 88%
“…5,22 Results of a recent (2019) metanalysis, 5 including 22 studies on adults analyzing different sports, showed that postexercise cTn release was positively correlated with exercise intensity (evaluated by the mean HR). Average 13,17 and peak HR 13 and race time 26,44 were positively associated with cTn postexercise rise, 14 regardless of the biomarker used. However, data are not univocal.…”
Section: Resultsmentioning
confidence: 86%
“…The ROCK signaling pathway participates in cell survival and cardiac hypertrophy, cardiac fibrosis, and cell apoptosis [15]. Some athletes may develop an extreme cardiac remodelling process, including atrial structure and function changes [12,13,26], worse ventricular performance post-effort [6], and appearance of arrhythmias in long-term followup [27,28]. Regarding the physiopathology of previous processes, the ROCK signaling pathway could play an important role in electrical property changes in atrial tissue (connexin expression), as Chen et al (2018) showed while studying the LA appendage in patients with and without atrial fibrillation [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of animal models of myocardial ischemia/reperfusion injury showed that fasudil, a Rho kinase inhibitor, exerts a cardioprotective effect including lowering of troponin-I elevation [31]. Multiple protocols have assessed troponin levels post-different intensities of exercise, but the results have different results and there have been different interpretations on the mechanism of troponin release, which probably depends on multiple individual mechanisms of adaptation to exercise [26,27,32]. In our protocol we did not find troponin-I elevation post-marathon race (troponin-I < 0.156 ng•mL −1 in all subjects).…”
Section: Discussionmentioning
confidence: 99%